Understanding the antimicrobial activity of selected disinfectants against methicillin-resistant Staphylococcus aureus (MRSA) - Aboualizadeh, Ebrahim (PLoS One, 2017)
Disinfectants and biocidal products have been widely used to combat Methicillin-resistant Staphylococcus aureus (MRSA) infections in homes and healthcare environments. Although disruption of cytoplasmic membrane integrity has been documented as the main bactericidal effect of biocides, little is known about the biochemical alterations induced by these chemical agents. In this study, we used Fourier transform infrared (FT-IR) spectroscopy and chemometric tools as an alternative non-destructive technique to determine the bactericidal effects of commonly used disinfectants against MRSA USA-300. FTIR spectroscopy permits a detailed characterization of bacterial reactivity, allowing an understanding of the fundamental mechanism of action involved in the interaction between bacteria and disinfectants. The disinfectants studied were ethanol 70% (N = 5), isopropanol (N = 5), sodium hypochlorite (N = 5), triclosan (N = 5) and triclocarban (N = 5). Results showed less than 5% colony forming units growth of MRSA treated with triclocarban and no growth in the other groups. Nearly 70,000 mid-infrared spectra from the five treatments and the two control (untreated; N = 4) groups of MRSA (bacteria grown in TSB and incubated at 37°C (Control I) / at ambient temperature (Control II), for 24h) were pre-processed and analyzed using principal component analysis followed by linear discriminant analysis (PCA-LDA). Clustering of strains of MRSA belonging to five treatments and the discrimination between each treatment and two control groups in MRSA (untreated) were investigated. PCA-LDA discriminatory frequencies suggested that ethanol-treated spectra are the most similar to isopropanol-treated spectra biochemically. Also reported here are the biochemical alterations in the structure of proteins, lipid membranes, and phosphate groups of MRSA produced by sodium hypochlorite, triclosan, and triclocarban treatments. These findings provide mechanistic information involved in the interaction between MRSA strains and hygiene products; thereby demonstrating the potential of spectroscopic analysis as an objective, robust, and label-free tool for evaluating the macromolecular changes involved in disinfectant-treated MRSA.